The discrimination of barbell weight for weightlifters - Tsai, Y.-C.; Yang, S.-K.; Chiu, H.-T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Ten college weightlifters were recruited in this study. The standard barbell weight (Ws) of each participant was set at 80% of personal best snatch record. The test barbell weights that include Ws, Ws+-1kg, Ws+-2kg, and Ws+-5kg were given randomly, then each lifter was asked to identify the difference between the test weight and standard weight. The discrimination was over 86% when the test weight was Ws+-5kg. For the test weight equal to the standard weight, the discrimination was significantly less than that of other test weights (p less than 01). Based on the results, the weightlifter seems to have good discrimination in the barbell mass at the difference of 5 kg. It seems that they could not be aware of the slight difference (ex: less than 2kg) of barbell mass by 80% of their best snatch record.